Behaviour of lump-grout material filled PVC tubular column under uniaxial compression. (21st November 2022) - Zhao, Hongchao; Ren, Ting; Remennikov, Alex
Highlights: Lump-grout material filled PVC tubular columns (LGFPT) was developed. The lumps can be either the coal rejects or waste rocks in the underground. LGFPTs are feature with strain-hardening behaviour with sufficient ductility. The water-to-powder ratio of cementitious grout affects the behaviour of LGFPTs. LGFPTs are not only cost-effective but also environmentally-friendly. Abstract: The hybrid structural form made of the polyvinyl chloride (PVC) and lump-grout (LG) material, termed LGFPT column, was developed as the alternative standing support for deep underground mines. To explore the mechanical response of this structural form under the uniaxial compression, various critical parameters (i.e., the water-to-powder ratio of the cementitious grout material, length-to-diameter ratio of the PVC tube, loading mode and loading speed) were investigated. Test results showed that the LGFPT column had an excellent ductility (>30% of the column length) associated with the strain hardening behaviour. Compared to its counterparts, the effect of the water-to-powder ratio of the grout material is most significant when the peak load of the LGFPT is evaluated. In parallel, the compressive behaviour of the cementitious grout material-filled PVC tubular (GFPT) column was investigated. When the ultimate axial compressive strength of the LGFPT and the GFPT are compared, the strength of the LGFPT was not significantly affected, although the cementitious grout material consumption of which has been reduced about 50% in volume. As a family member of the standing support systems, the LGFPT is an ideal candidate to be used in underground mines attributed to its cost-effective and environmentally-friendly.